Family and Fertility in Puerto Rico A Study of the Lower Income Group - Stycos, J. Mayone (Columbia University Press, 1955)
Covers a wide range of variables hypothetically bearing on fertility while emphasizing sexual norms, character structure, the fertility belief system, and birth control practices, as they are all influenced by the family